Synergistic effect of atorvastatin and Cyanidin-3-glucoside on angiotensin II-induced inflammation in vascular smooth muscle cells - Rungusa Pantan (2018)
© 2016 Elsevier Inc. Statins have often been used in atherosclerosis treatment because of its pleiotropic effects on inflammation. However, some adverse effects of high doses of statin show reverse effects after withdrawal. Cyanidin-3-glucoside (C3G) is a powerful anti-inflammation and antioxidant that has been of interest for use in combination with low doses of statin, which may be alternative treatment for atherosclerosis. The objective is to investigate the synergistic effect of atorvastatin and C3G in angiotensin II (Ang II)-induced inflammation in vascular smooth muscle cells. Human aortic smooth muscle cells (HASMCs) were exposed to Ang II with or without atorvastatin and C3G alone, or in combination. The results revealed that the combination of atorvastatin and C3G produces synergism against inflammation and oxidative stress. The mechanism of the combination of atorvastatin and C3G suppressed the translocation of the p65 subunit of NF-κB from cytosol to nucleus, and attenuated the expression of proteins including inducible nitric oxide synthase, intracellular adhesion molecule 1(ICAM-1), and vascular cell adhesion molecule 1(VCAM-1), in addition to nitric oxide (NO) production. Moreover, C3G exerts the antioxidative properties of atorvastatin through down-regulating NOX1 and promoting the activity of the Nrf2-ARE signaling pathway and downstream proteins including heme oxygenase (HO-1), NAD(P)H:quinoneoxidoreductase 1 (NQO-1), and glutamate-cysteine ligase catalytic subunit (γ-GCLC), besides increasing the activity of superoxide dismutase (SOD) enzymes. Taken together, these results suggest that a combination of low dose statins and C3G might serve as a potential regulator of the atherosclerosis process which is mediated by attenuating oxidative stress, thereby inhibiting NF-κB and activating Nrf2 signaling pathways induced by Ang II.